High-temperature oxidation behavior of a Ti5Si3-incorporated MoSiBTiC alloy. (October 2020) - Nan, Xi; Zhao, Mi; Lu, Yuanyuan; Sekido, Nobuaki; Yoshimi, Kyosuke
Abstract: The oxidation behavior of a Ti5 Si3 -incorporated MoSiBTiC alloy (38Mo–30Ti–17Si–10C–5B, at.%) was systematically studied in the temperature range of 700–1000 °C. Temperature dependence of oxidation kinetics and oxide scale formation was revealed for this alloy. The oxidation kinetics at 700 °C featured an initial transient stage of weight gain and then switched to weight loss. At 800 °C, the oxidation kinetics featured an initial transient stage with fast weight loss, a steady stage with small weight loss, and an acceleration stage leading to catastrophic failure. At 900 and 1000 °C, the alloy exhibited a rapid transient weight loss as followed by a decreased weight loss fitting to parabolic kinetics. The scales that formed at 700–1000 °C mainly consisted of rutile TiO2 and amorphous SiO2 . The high viscosity of SiO2 at 700 and 800 °C caused the formation of porous and microcracked oxide scales while the occurrence of viscous flow during oxidation at 900–1000 °C promoted the formation of dense and protective scales.